Pride and guilt as place-based affective antecedents to pro-environmental behavior - Shipley, Nathan J.; van Riper, Carena J.; Stewart, William; Chu, Maria; Stedman, Richard C.; Dolcos, Florin (Frontiers in Psychology, 2023)
The interrelated concepts of place attachment and place meaning are antecedents to pro-environmental behavior and essential for supporting decisions that foster relationships between people and places. Previous research has argued that affect is instrumental in conceptualizing place-related phenomena but has not yet been considered in terms of discrete emotions. We disentangled the empirical relationships between concepts of place and the emotions of pride and guilt to understand how they collectively contributed to individuals’ decisions about environmental sustainability. Specifically, we conducted an online survey of residents living the Midwestern US and asked questions about residents’ attachments to places and their place-related behavior. We then tested a latent variable path model with first- and second-order factors that shaped the behavioral intentions of survey respondents, as well as evaluated the psychometric properties of a place meaning scale, to uncover the range of reasons why human-nature relationships were formed. Our findings show that multiple place meanings predicted place attachment, which in turn predicted the discrete emotions of pride and guilt. Place attachment, pride, and guilt positively correlated with pro-environmental behavior. We also observed that the relationship between multi-dimensional conceptualizations of place attachment and behavioral intentions was partially mediated by pride but not guilt, as hypothesized in response to the broaden and build theory of positive emotions. This study develops theoretical insights to clarify how cognitive-emotional bonding can lead people to behave in more environmentally friendly ways.